Spectral changes induced by pH variation of aqueous extracts derived from biomass burning aerosols: Under dark and in presence of simulated sunlight irradiation. (July 2018) - Cai, Jing; Zhi, Guorui; Yu, Zhiqiang; Nie, Peng; Gligorovski, Sasho; Zhang, Yuzhe; Zhu, Like; Guo, Xixiang; Li, Pei; He, Tan; He, Youjiang; Sun, Jianzhong; et al.
Abstract: Water soluble organic carbon (WSOC) can significantly influence the aerosol optical properties and the aqueous phase chemistry in cloudwater, fogwater and aerosol liquid water. Here, we examine how the changing pH (in acidic range) affects the absorption spectra of aqueous extracts from field biomass burning aerosols, under dark conditions and in presence of simulated sunlight illumination. The observation under dark conditions indicates that pH variation from 2 to 5 induces significantly enhanced light absorbance in the wavelength ranges of 235–270 nm and 300–550 nm, whereas the light absorbance decreased in the range of 270–300 nm, which might be partially ascribed to the deprotonation of carboxylic acids and phenols. During the extract photolysis, light absorption exhibits photo-bleaching below 380 nm and photo-enhancement above 380 nm, indicating that at acidic levels (pH = 2–5), the particle extracts could undergo a significant composition evolution leading to a modification of absorptive properties. Meanwhile, after 12 h-photolysis, the acidity ([H + ]) normalized by WSOC concentration in aqueous extracts ([WSOCae ]) increased with a variation of Δ[H + ]/[WSOCae ]=(3.7 ± 0.7) × 10 −7  mol mgC −1 (mean ± standard deviation), suggesting the formation of new acidic substances. Although these findings were acquired in aqueous solutions more relevant to cloud and fog water, the similar evolution likely occurs in wetted aerosols. This calls more attention to the effect of acidity on the wetted aerosols in order to better estimate the aerosol radiative forcing. Highlights: Absorption spectra of aqueous extract from biomass burning aerosol are pH-sensitive. With light illumination, spectral evolution occurs at acidic conditions. Photochemical evolution on the particle extract enhances aqueous acidity.